Kinematic comparison for single shooting and fast shooting in traditional archery - Muhammad Shahimi Ariffin,; Azmin Sham Rambely,; Noratiqah Mohd Ariff,; Rohilah Sahak,; Syazwana Aziz,; Muhammad Athif Mat Zin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The aim of this paper is to compare performance single shooting (SS) and fast shootings (FS) in Mameluke traditional archery. A group of 10 elites archer participated in the study with total of 100 shots perform. Joint angles of bow arm (BA) and draw arm (DA) are measured to compare the similarities and differences between the two shooting techniques. Angles data are aligned using Functional Data Analysis (FDA) and single averaged curve representating each shot is compared. Performance measurement such as Pearson correlation coefficient (r), Sprague and Geers metrics are used. Result shows that value of r falls in a range of 0.7 to 0.99, while Sprague and Geer metrics of magnitude and phase are between [0.03,0.14] and [0.03,0.16], respectively. The metrics values show a near-zero value and r is closed to one. Thus, the two shots are found to be relatively similar despite the difference biomechanically in completing 10 shots for each shooting technique.